Making existing technology safer in healthcare. (6th August 2010) - Newton, Richard C; Mytton, Oliver T; Aggarwal, Rajesh; Runciman, William B; Free, Michael; Fahlgren, Bjorn; Akiyama, Masanori; Farlow, Barbara; Yaron, Sara; Locke, Gerad; Whittaker, Stuart
Abstract : Background: Technology, equipment and medical devices are vital for effective healthcare throughout the world but are associated with risks. These risks include device failure, inappropriate use, insufficient user-training and inadequate inspection and maintenance. Further risks within the developing world include challenging conditions of temperature and humidity, poor infrastructure, poorly trained service providers, limited resources and supervision, and inappropriately complex equipment being supplied without backup training for its use or maintenance. Methods: This document is the product of an expert working group established by WHO Patient Safety to define the measures being taken to reduce these risks. It considers how the provision of safer technology services worldwide is being enhanced in three ways: through non-punitive and open reporting systems of technology-related adverse events and near-misses, with classification and investigation; through healthcare quality assessment, accreditation and certification; and by the investigation of how appropriate design and an understanding of the conditions of use and associated human factors can improve patient safety. Results and discussion: Many aspects of these steps remain aspirational for developing countries, where highly disparate needs and a vast range of technology-related problems exist. Here, much greater emphasis must be placed on failsafe, durable and user-friendly design—examples of which are described.